EFEKTIVITAS PENGGUNAAN MEDIA PAPAN WAKTU PADA PEMBELAJARAN PENGHITUNGAN WAKTU BAGI SISWA KELAS III SEKOLAH DASAR - Reza Syehma Bahtiar (Jurnal Bidang Pendidikan Dasar, 2019)
The purpose of this research is to know the results of the students after using media Board of time in learning the calculation time. This research is a descriptive qualitative study types. The instruments used in this research are test results of the study, observation, and question form. Based on the results of the research that has been done that student learning outcome is said to be completely in classical because percentage earned more than completeness of classical learning outcome criteria as many 83.79% of students with a total number of 31 students who Mastery Learning and 6 students who do not pass the study. The observation activities of the teacher in managing learning counting time using media Board learning time is said to be very good because the results obtained as many 92.5. The observation activities of students in learning the calculation time using media Board learning time is said to be very good because the percentage obtained in the amount of 90%. While the response is given by students when students use learning media Board time is said to be positive because the percentage obtained of 82.64%.